A systematic review of progenitor survival and maturation in Parkinsonian models - Giulia Comini; Eilís Dowd (Neural Regeneration Research)
Stem cell–based brain repair is a promising emergent therapy for Parkinson’s disease based on years of foundational research using human fetal donors as a cell source. Unlike current therapeutic options for patients, this approach has the potential to provide long-term stem cell–derived reconstruction and restoration of the dopaminergic input to denervated regions of the brain allowing for restoration of certain functions to patients. The ultimate clinical success of stem cell–derived brain repair will depend on both the safety and efficacy of the approach and the latter is dependent on the ability of the transplanted cells to survive and differentiate into functional dopaminergic neurons in the Parkinsonian brain. Because the pre-clinical literature suggests that there is considerable variability in survival and differentiation between studies, the aim of this systematic review was to assess these parameters in human stem cell-derived dopaminergic progenitor transplant studies in animal models of Parkinson’s disease. A defined systematic search of the PubMed database was completed to identify relevant studies published up to March 2024. After screening, 76 articles were included in the analysis from which 178 separate transplant studies were identified. From these, graft survival could be assessed in 52 studies and differentiation in 129 studies. Overall, we found that graft survival ranged from < 1% to 500% of cells transplanted, with a median of 51% of transplanted cells surviving in the brain; while dopaminergic differentiation of the cells ranged from 0% to 46% of cells transplanted with a median of 3%. This systematic review suggests that there is considerable scope for improvement in the differentiation of stem cell–derived dopaminergic progenitors to maximize the therapeutic potential of this approach for patients.